ChemInform Abstract: Selective Nanocrystal Synthesis and Calculated Electronic Structure of All Four Phases of Copper—Antimony—Sulfide. Issue 29 (22nd July 2014) - Ramasamy, Karthik; Sims, Hunter; Butler, William H.; Gupta, Arunava
Abstract Nanocrystals of all four phases of the Cu—Sb—S system are prepared by a colloidal hot‐injection method.